Mucosa and microbiota – the role of intrinsic parameters on intestinal wound healing - Kelm, Matthias; Anger, Friedrich (Frontiers in Surgery, 2022)
Mucosal healing in the gut is an essential process when it comes to chronic inflammatory disorders such as inflammatory bowel diseases (IBD) but also to the creation of intestinal anastomosis. Despite an improvement of surgical techniques, the rates of anastomotic leakage remain substantial and represent a significant health-care and socio-economic burden. Recent research has focused on intrinsic factors such as mucosal linings and differences in the intestinal microbiota and identified specific endoluminal bacteria and epithelial proteins which influence intestinal wound healing and re-establishment of mucosal homeostasis. Despite the lack of large clinical studies, previous data indicate that the identified bacteria such as aerotolerant lactobacilli or wound-associated Akkermansia muciniphila as well as epithelial-expressed sialyl Lewis glycans or CD47 might be critical for wound and anastomotic healing in the gut, thus, providing a potential novel approach for future treatment strategies in colorectal surgery and IBD therapy. Since microbiota and mucosa are interacting closely, we outline the current discoveries about both subsets in this review together to demonstrate the significant interplay